Research in the Training of Traditional Chinese Medicine Talents in the Whole Life Cycle Based on the Perspective of Needs - Sai, Liu; Xiao, Yiting (Asia Pacific Economic and Management Review, 2026)
Purpose: To understand the current situation of demand for traditional Chinese medicine(TCM) talents throughout the entire life cycle in China, the training and supply models, and the talent team situation, analyze the gap between demand and supply of traditional Chinese medicine talents, and put forward some suggestions and ideas to make the supply and demand of TCM talents in the whole life cycle basically reach the balance of supply and demand. Methods: According to the statistical yearbook of Traditional Chinese Medicine and National Bureau of Statistics of the People's Republic of China using the methods of literature analysis to analyze the survey data. Results: The demand for Chinese medicine professionals will continue to increase for a long time to come, due to objective and subjective reasons such as national policies, industry development, population ageing and residents; personal preferences, at present, there are some shortcomings in the whole life-cycle training process of prevention, diagnosis, treatment, rehabilitation and health care for talents of Chinese medicine, and the existing system and mechanism in the Chinese medicine industry is unreasonable, lead to the whole life cycle of Chinese medicine talent supply and demand mismatch. Conclusion: Through the improvement and reform of Chinese medicine colleges, trades and society, the Chinese medicine talents can be developed comprehensively from prevention to health care and rehabilitation, secondly, the industry optimizes the employment and evaluation mechanism to make Chinese medicine talents play a role, and finally the social strata to change the concept of employment. To build a high-quality team of Chinese medicine talents, and to enable the institutions to train the talents to meet the needs of the community, the supply and demand of the dynamic equilibrium state.